SMRT long reads and Direct Label and Stain optical maps allow the generation of a high-quality genome assembly for the European barn swallow (Hirundo rustica rustica). Issue 1 (29th November 2018) - Formenti, Giulio; Chiara, Matteo; Poveda, Lucy; Francoijs, Kees-Jan; Bonisoli-Alquati, Andrea; Canova, Luca; Gianfranceschi, Luca; Horner, David Stephen; Saino, Nicola
Abstract: Background: The barn swallow ( Hirundo rustica ) is a migratory bird that has been the focus of a large number of ecological, behavioral, and genetic studies. To facilitate further population genetics and genomic studies, we present a reference genome assembly for the European subspecies ( H. r. rustica ). Findings: As part of the Genome10K effort on generating high-quality vertebrate genomes (Vertebrate Genomes Project), we have assembled a highly contiguous genome assembly using single molecule real-time (SMRT) DNA sequencing and several Bionano optical map technologies. We compared and integrated optical maps derived from both the Nick, Label, Repair, and Stain technology and from the Direct Label and Stain (DLS) technology. As proposed by Bionano, DLS more than doubled the scaffold N50 with respect to the nickase. The dual enzyme hybrid scaffold led to a further marginal increase in scaffold N50 and an overall increase of confidence in the scaffolds. After removal of haplotigs, the final assembly is approximately 1.21 Gbp in size, with a scaffold N50 value of more than 25.95 Mbp. Conclusions: This high-quality genome assembly represents a valuable resource for future studies of population genetics and genomics in the barn swallow and for studies concerning the evolution of avian genomes. It also represents one of the very first genomes assembled by combining SMRT long-read sequencing with the new Bionano DLS technology for scaffolding. The quality of this assembly demonstrates the potential of this methodology to substantially increase the contiguity of genome assemblies.